Multi-criterion evaluation of territorial suitability for beekeeping using geographic information systems in the Alto Pozuzo basin, Peru - Navarro-Espinoza, Esteban (2026)
The identification of suitable areas for beekeeping is essential for territorial planning and the sustainable management of ecosystem services associated with pollination. This study aimed to evaluate territorial suitability for beekeeping in the Alto Pozuzo watershed, Peru, through the integration of Geographic Information Systems (GIS), Multi-Criteria Evaluation (MCE), and the Analytic Hierarchy Process (AHP). The spatial model integrated variables related to land use and land cover, elevation, slope, temperature, precipitation, and distance to water sources. The criteria were standardized and weighted using expert judgment, generating a continuous beekeeping suitability index in ArcGIS 10.8. Additionally, spatial autocorrelation analyses (Moran’s I and LISA) and territorial validation were conducted using productive information from 40 georeferenced apiaries. The land use and land cover classification achieved an overall accuracy of 80.0% and a Kappa coefficient of 0.76. The results revealed a heterogeneous spatial distribution of beekeeping suitability, with medium and high suitability categories predominating (67.94% of the watershed area). The most favorable areas were associated with diverse vegetation cover, intermediate climatic conditions, and proximity to water resources. Furthermore, significant spatial clusters of high suitability were identified, along with a positive relationship between the territorial suitability index and annual honey production. It is concluded that the integration of GIS, MCE, AHP, and spatial analysis constitutes a robust and replicable approach for the sustainable planning of beekeeping in tropical montane ecosystems.